Sustainable cultivation of rice: Challenges and opportunities - Banerjee, Nandita; Kumar, Sanjeev (Indian Farming, 2023)
As a universal call to action to end poverty, protect the planet and ensure peace and prosperity by 2030, the United Nations have adopted 17 Sustainable Development goals (SDGs). In accord with these goals, India being an emerging global leader is truly committed to achieve these SDGs. Although India is the fourth largest economy in terms of GDP, its world ranking in SDG index has gone down from 117 to 120 rank in 2022. Rice is the third largest crop which provides one-fifth of the total calories consumed in the world. However, present day cultivation methods of rice contribute to global warming through the release of greenhouse gases (GHGs) like methane and nitrous oxide more than other crops and also place a heavy demand on the available freshwater resources. Hence, a shift to sustainable cultivation practices can act as a key driver for India to achieve SDGs by 2030.